A Zeb1/MtCK1 metabolic axis controls osteoclast activation and skeletal remodeling. (27th February 2023) - Zhu, Lingxin; Tang, Yi; Li, Xiao‐Yan; Kerk, Samuel A; Lyssiotis, Costas A; Feng, Wenqing; Sun, Xiaoyue; Hespe, Geoffrey E; Wang, Zijun; Stemmler, Marc P; Brabletz, Simone; Brabletz, Thomas; et al.
Abstract: Osteoclasts are bone‐resorbing polykaryons responsible for skeletal remodeling during health and disease. Coincident with their differentiation from myeloid precursors, osteoclasts undergo extensive transcriptional and metabolic reprogramming in order to acquire the cellular machinery necessary to demineralize bone and digest its interwoven extracellular matrix. While attempting to identify new regulatory molecules critical to bone resorption, we discovered that murine and human osteoclast differentiation is accompanied by the expression of Zeb1, a zinc‐finger transcriptional repressor whose role in normal development is most frequently linked to the control of epithelial‐mesenchymal programs. However, following targeting, we find that Zeb1 serves as an unexpected regulator of osteoclast energy metabolism. In vivo, Zeb1‐null osteoclasts assume a hyperactivated state, markedly decreasing bone density due to excessive resorptive activity. Mechanistically, Zeb1 acts in a rheostat‐like fashion to modulate murine and human osteoclast activity by transcriptionally repressing an ATP‐buffering enzyme, mitochondrial creatine kinase 1 (MtCK1), thereby controlling the phosphocreatine energy shuttle and mitochondrial respiration. Together, these studies identify a novel Zeb1/MtCK1 axis that exerts metabolic control over bone resorption in vitro and in vivo . Synopsis: Osteoporosis and similar bone‐wasting conditions can be caused by an increase in osteoclast‐mediated bone resorption. Here, we learn that both murine and human osteoclasts are activated by a Zeb1‐dependent regulation of mitochondrial energy metabolism. The transcription factor Zeb1 is a negative regulator of giant multinucleated osteoclast‐mediated skeletal remodeling. Zeb1 regulates mitochondrial energy metabolism in myeloid lineage‐derived osteoclasts. The mitochondrial creatine kinase MtCK1 is a transcriptional target of Zeb1 that enables bone resorption by buffering ATP availability. Abstract : The transcription factor Zeb1 influences bone development by regulating mitochondrial ATP availability.